(untitled) (JOURNAL OF THERAPY AND REHABILITATION, 2025)
Chemotherapy-induced peripheral neuropathy (CIPN) is characterized by sensory, motor, and autonomic impairments that reduce patients’ quality of life and may lead to chemotherapy dose reduction or treatment discontinuation. Increasing attention in the management of CIPN is being directed toward non-pharmacological approaches, particularly physical therapy. The aim of this study was to conduct a comparative analysis of contemporary scientific literature and international clinical practice guidelines regarding physical therapy in patients with CIPN. The methods included an analysis of clinical recommendations and systematic reviews published by leading international oncological and sports medicine organizations (ASCO, ACSM), as well as national regulatory bodies from Germany, Japan, Canada, and Israel. The analysis focused on types of physical therapy interventions, exercise prescription parameters, and safety thresholds during chemotherapy. CIPN is most commonly associated with the use of platinum-based agents, taxanes, vinca alkaloids, and proteasome inhibitors. The literature indicates that therapeutic exercise, including aerobic, resistance, and balance training, may reduce the severity of CIPN symptoms and improve functional capacity and quality of life. International guidelines emphasize the necessity of individualized exercise programs and strict adherence to safety protocols. Physical therapy is therefore considered a safe component of oncological care for patients with CIPN; however, its implementation in clinical practice requires compliance with internationally recognized safety recommendations.